Macroinvertebrados bentônicos e fatores físicos e químicos como indicadores de qualidade da água da Bacia do Alto Jacaré-Guaçu (SP) - Andrade, Carolina Cunha (2009)
Physical, chemical and biological variables from 6 pre-selected sampling stations, including rivers and one reservoir at the Jacaré-Guaçu (SP) watershed, were sampled during the months of July, 2007 and March, 2008. The macroinvertebrates samples were collected from natural substract with Ekman-Birge dredger and also from vegetation with kiknet net. The goal of this study was to relate richness and abundance of benthic macroinvertebrates (identified until the level of family, except for Chironomidae, which was identified until the level of gender) with water quality by using metrics and biological index. These were applied in order to verify the relation between macroinvertebrates communities and water quality, which was analyzed through physical and chemical methods. In most preserved places, with low values of electrical conductivity and total phosphorus, a greater richness and diversity of benthic macroinvertebrates. On the other way, in places under influence of sewage, a greater dominance of organisms that are tolerant to organic pollution, such as Oligochaeta, Chironomidae and Hirudinea was found. Among Chironomidae family, Tanytarsini and Tanypodinae were associated to better water quality, while Chironomus gr. decorus occurred in great abundance on places under sewage discharge influence. Among the indexes applied, HBI provided the best answers, matching the physical andn chemical results.